2014
DOI: 10.1007/s11230-014-9506-3
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis eothenomysi n. sp. (Apicomplexa: Sarcocystidae) from the large oriental vole Eothenomys miletus (Thomas) (Cricetidae: Microtinae) from Anning, China

Abstract: Fifty-six oriental voles, Eothenomys miletus (Thomas), were collected in Anning prefecture of Yunnan Province (China) between March 2012 and December 2013 and examined for the presence of sarcocysts. Sarcosysts of a new species, Sarcocystis eothenomysi n. sp., were found in 14 out of 56 E. miletus (25%); they possessed a striated cyst wall, c.1-2 μm thick. Under transmission electron microscopy the cysts of S. eothenomysi exhibited numerous small, irregular protrusions, which may appear T-shaped in some sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In the present study, an additional Sarcocystis species was identified in the large oriental vole, adding to the species reported recently by Hu et al (2014). Transmission experiments and the 18S rDNA sequence similarity between cyst and oöcysts indicated that the beauty rat snake is a definitive host of S. clethrionomyelaphis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, an additional Sarcocystis species was identified in the large oriental vole, adding to the species reported recently by Hu et al (2014). Transmission experiments and the 18S rDNA sequence similarity between cyst and oöcysts indicated that the beauty rat snake is a definitive host of S. clethrionomyelaphis.…”
Section: Discussionsupporting
confidence: 78%
“…The 18S rRNA gene was amplified with primers S1/B designed by Fischer & Odening (1998) and Medlin et al (1988), respectively. Polymerase chain reaction (PCR) amplifications were performed as described previously (Hu et al, 2014). PCR products were gelpurified and cloned using PMD-19T vector (TakaRa).…”
Section: Methodsmentioning
confidence: 99%
“…tupaia possesses a smooth type 1 wall ( Xiang et al, 2010 ), the ultrastructure of the present species clearly reveals a thick striated wall with VP that share structural elements with the tightly packed protrusions of wall type 12. Because our phylogenetic results indicate a sister taxon relationship with three previously described Sarcocystis species that undergo a snake-rodent life cycle ( Slapeta et al, 2003 ; Hu et al, 2012 , 2014 , 2015 ; Wassermann et al, 2017 ), morphological comparison with those species is implicit: S . singaporensis , S .…”
Section: Resultsmentioning
confidence: 88%
“…pantherophisi ( Verma et al, 2017 ) and S . eothenomysi ( Hu et al, 2014 ), cystozoites of the Sarcocystis sp. infecting Bornean treeshrews are markedly smaller: similar in size to species with a snake-lizard life cycle, where cystozoites are between 4 and 7 μm long ( Matuschka, 1981 ; Abdel-Ghaffar et al, 1990 ; Modry et al, 2000 ; Morsy et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the phylogenetic tree based on 18S rRNA sequences, S. pantherophisi n. sp. Sequences clustered consistently with Sarco-cystis eothenomysi (from a vole in China, and suspected to have a snake definitive host; Hu et al, 2014) and, with less bootstrap support, Sarcocystis nesbitti (nonhuman primates as intermediate hosts and humans as aberrant hosts; rodents have been hypothesized as natural intermediate hosts and snakes as natural definitive hosts; Dubey et al, 2015), and Sarcocystis atheridis (Fig. 5).…”
Section: Pcr and Dna Analysismentioning
confidence: 97%